Enhancement of flow properties, solubility, and dissolution of the atazanavir by spherical crystallization - Jadhav, Ashok T; Pekamwar, Sanjay S. (Creative Pharma Assent, 2025)
Background: The present work aimed to develop spherical agglomerates of Atazanavir (ATZR) with enhanced flow properties, compressibility, solubility, and dissolution. 22 full factorial design approach was employed to develop agglomerates. Methodology: ATZR spherical agglomerates were prepared using bridging solvent Benzene, methanol, HPMC and evaluation for different properties. Then, ATZR immediate release (IR) capsules were formulated using spherical agglomerate, wet granulation, and direct compaction methods. Results and discussion: The spherical agglomerates resulted in a significant enhancement of micromeritic properties. The drug content was ranged from 91.9 % (SAA6) to 97% (SAA2). Drug content and solubility (4.88 to 39.89 mg/ml) were directly related to the concentration of HPMC and inversely related to benzene concentration (p<0.05). Nearly 10.12-fold enhancement in solubility of ATZR was found with spherical agglomerates. FTIR analysis demonstrated excellent compatibility between the drug and the polymer. XRD results indicated the amorphization of pure ATZR during agglomeration. The agglomerates exhibited spherical particle morphology. DSC analysis confirmed the effective encapsulation of the drug. Nearly 100% release was observed within 10 minutes from the F1 capsule formulation containing ATZR spherical agglomerates. Conclusion: The optimized SAA2 spherical agglomerates were utilized to manufacture immediate-release capsules via direct filling (F1). Spherical agglomerates significantly enhanced the flow properties and compressibility of the blend compared to pure ATZR. Drug release from the F1 batch was notably faster than F2 and F3 formulations. The study demonstrates the substantial improvement in flow properties, compressibility, solubility, and dissolution of ATZR using spherical agglomerates.